Análisis Financiero a la Asociación Agroartesanal de Productores Ecológicos de Palanda y Chinchipe, Períodos 2021-2022. - Segura Soto, Lisbeth Katherin (2024)
The present Curricular Integration Work titled: "FINANCIAL ANALYSIS OF THE ECOLOGICAL PRODUCERS' AGROARTISAN ASSOCIATION OF PALANDA AND CHINCHIPE, 2021-2022 PERIODS," was developed with the purpose of fulfilling the overall objective of conducting a financial analysis of the Ecological Producers' Agroartisan Association of Palanda and Chinchipe, for the periods 2021-2022. For this purpose, the financial analysis method was applied, which will help understand the financial health of the Association through the application of vertical and horizontal analysis, as well as the use of financial indicators. In compliance with the first specific objective, vertical and horizontal analysis was carried out by calculating the variations presented in each item that makes up the financial and economic structure. It was evident that in both periods, the majority of liquid assets are concentrated in accounts and receivables. Similarly, it is observed that the liabilities, which consist exclusively of current liabilities in both periods, show an increase in the share of obligations committed to third parties in 2022. Additionally, there are high levels of costs in 2021 and overruns in 2022 compared to income, indicating losses in profitability. For the second specific objective, financial indicators such as liquidity, activity, indebtedness, and profitability were applied. The Association's liquidity shows positive values, although there is some dependency on inventories and accounts receivable to meet contracted obligations. Regarding its activity, there is a recovery of accounts receivable in less than two months. By applying indebtedness indicators, it was determined that the Association is not capable of covering all its liabilities or taking on new debts. Profitability indicators revealed that the Association's performance is not favorable due to the high levels of operational costs presented in the period. Finally, for the third objective, a financial analysis report was presented, encompassing a summary of the results obtained through the application of vertical and horizontal analysis, as well as financial indicators. The report includes relevant conclusions and recommendations that reveal the economic and financial situation of the Association, aiming to improve weaknesses and 5 leverage strengths. This will serve as a guide for the members and contribute to making more informed decisions for the Association's benefit.